PHYSICAL AND MECHANICAL PROPERTIES OF NONWOVEN MATERIALS BASED ON NATURAL SILK (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The article discusses the use of non-recyclable fibrous waste of natural silk in consumer textile products, in particular, in the production of non-woven materials, with the subsequent production of consumer goods. Primary and secondary silk fibers are combined with other chemical fibers to produce products. The thermopress process was used to create the nonwoven material. High physical and mechanical qualities of materials produced from primary and secondary fibers were revealed by analysis of experimental data.